A review of the effects of weak interfaces on crack propagation in rock: From phenomenon to mechanism. (15th March 2022) - Ju, Minghe; Li, Xiaofeng; Li, Xing; Zhang, Guanglei
Graphical abstract: Highlights: The effects of weak interfaces in rock-like materials and structures on crack propagation are systematically reviewed. The intrinsic mechanism of interface effects on crack propagation is discussed in terms of crack deflection criterion. Weak interface effects on rock dynamic failure are reviewed and the remaining issues are extracted. Abstract: This article reviews the effect of weak interfaces on crack propagation in rock and some other analogous brittle materials from phenomenon to mechanism. In this review, a variety of fracture patterns (in terms of a propagating crack interacting with a pre-existing interface) are classified, followed by the introduction of some critical influence factors, e.g. strength and toughness of interface, interface angle, interlayer effect, elastic mismatch, dynamic loading, and confining stress. Then, the effects of weak interfaces on the quasi-static and dynamic mechanical behaviors of rock are briefly reviewed. Thereafter, the mechanism of action of weak interfaces on crack propagation in rock is discussed in terms of crack deflection criteria. Finally, some conclusions and outlooks on the research of the effects of weak interfaces on crack propagation in rock are provided.